Creatine metabolism: detection of creatine and guanidinoacetate in saliva of healthy subjects. - Martínez, L.D. (2016)
Creatine (Cr) plays an important role in storage and transmission of phosphate-bound energy. Cerebral creatine deficiency syndromes comprise three inherited defects in Cr biosynthesis and transport. The aim of this study was to investigate whether Cr and Guanidinoacetate (GAA) can be detected in saliva of healthy subjects and to establish the relationship between salivary and plasma levels of these molecules. An adapted gas chromatography (GC) method is described for the quantification of Cr and GAA biomarkers in saliva. Reference values were established for GAA and Cr in saliva. These values were age dependent (p= 0.001). No difference between genders was observed. We detected a difference between GAA and Cr concentrations in saliva and in plasma. The GC method for simultaneous determination of GAA and Cr in human saliva is fast, reliable, sensitive, non-invasive and precise to use as a biochemical approach in early detection of cerebral creatine deficiency syndromes.